Percutaneousinsertion technique: rapid advances of peritoneal dialysis catheterization - Zhou Min; Zhao Jin-wen (Linchuang shenzangbing zazhi)
Successful peritoneal dialysis（PD）depends upon a well-functioning PD catheter and proper PD catheterization plays a decisive role.Recently percutaneous catheter insertion becomes popular because of its simplicity, mini-invasiveness and fewer complications.It promotes the popularization and development of PD especially at grass-root hospitals.The review summarized the advantages and clinical trial advances of percutaneous PD catheterization.